Evidence of play behavior in captive California two-spot octopuses, Octopus bimaculoides. - Katarina Jarmoluk; Galit Pelled (PLoS ONE)
Play is considered to be an essential part of development that supports learning, memory, and the development of flexible behavioral strategies. It may also serve as an informative factor in assessing an animal's welfare state and in improving care and husbandry practices. An increasing number of non-mammalian species have been discovered to engage in play behavior, including several cephalopod species. Here, we characterized play behavior in wild-caught, laboratory-housed California Two-Spot Octopuses, Octopus bimaculoides, a species with growing relevance as a model in biomedical research, with the goal of establishing a behavioral repertoire and encouraging further research into the behavior and welfare of this species.